2002
DOI: 10.1097/00007632-200212010-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mental Processing and Pacing on Spine Loading

Abstract: Mental processing stress acted as a catalyst for the biomechanical responses, leading to intensified spine loading. Mental stress appeared to occur as a function of time pressures on task performance and resulted in less controlled movements and increases in trunk muscle coactivation. These adjustments significantly increased spine loading. These results suggest a potential mechanism for the increase in low back pain risk resulting from psychosocial stress caused by modern work demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
72
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 104 publications
3
72
2
Order By: Relevance
“…However, the increased stretch reflex sensitivity during increased MSNA may have potentially adverse effects. Interestingly, increased spine loading was observed during a stressful standardized lifting task compared with nonstressful conditions (5,19). The authors suggest that mental stress might cause an overreaction of the musculoskeletal system, manifesting itself through less controlled motions and increased muscle coactivation.…”
Section: Discussionmentioning
confidence: 97%
“…However, the increased stretch reflex sensitivity during increased MSNA may have potentially adverse effects. Interestingly, increased spine loading was observed during a stressful standardized lifting task compared with nonstressful conditions (5,19). The authors suggest that mental stress might cause an overreaction of the musculoskeletal system, manifesting itself through less controlled motions and increased muscle coactivation.…”
Section: Discussionmentioning
confidence: 97%
“…The psychological stress of back pain may then result in long-term disability due to pain. Additionally, a previous biomechanical study showed that psychological stress is associated with increased spinal loading and injury risk 26) . Based on these results, it can be considered that a physician's advice to rest makes patients less positive and optimistic than advice to stay active, leading to an increase in psychological stress, which results in an increase in spinal loading and injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…Physical demands increase the odds of injury [Fredriksson et al, 2002; due to creation of compression, rotation, and shear forces that exceed body tolerances [Marras et al, 1999;Forde et al, 2002;Hoozemans et al, 2002]. Psychological job demands can amplify the effects of physical exertion [Ariens et al, 2002;Davis et al, 2002;Devereux et al, 2002]. Furthermore, lack of ability to control time on and off work-which is inherent in mandatory overtime and on-call work-disproportionately affects women, who may have additional home responsibilities such as child care [Ala-Mursula et al, 2004;Jansen et al, 2004].…”
mentioning
confidence: 99%